Fade to Grey. The Grey Pottery in Northern Italy between 6th and 1st centuries B.C. (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
This paper offers an overview on the phenomenon of gray pottery in northern Italy, mainly based on new features emerged in literature over the last decade. Several pots were produced in gray ware vessels for the consumption of food and drink, even during banquets and symposia. It begins in northern Etruria and within the Po Valley during the 6th century BC, then spreading and increasing during the following centuries until the Romanisation, especially in the Veneto region and in the North-East. The gray pottery main feature is to locally imitate the most fashionable shapes of any period, beginning from bucchero ware and attic black and figured pottery, until black-gloss ware of the Hellenistic and Roman era. Gray ware was very popular especially within 5th century BC rural settlements which were not wealthy enough to purchase complete sets of imported pottery. Otherwise gray pottery became widespread after the Gallic invasions climaxed in 388 BC, when trade routes and social structures deeply changed.
Keywords: grey pottery; grey bucchero pottery; black-gloss ware; Etruscans; Po Valley; banquet and symposium